Probabilistic evaluation of observed earthquake damage data in Turkey - Sengezer, Betul; Ansal, Atilla (SPRINGER, 2007)
Empirical, theoretical or hybrid methods can be used for the vulnerability analysis of structures to evaluate the seismic damage data and to obtain probability damage matrices. The information on observed structural damage after earthquakes has critical importance to drive empirical vulnerability methods. The purpose of this paper is to evaluate the damage distributions based on the data observed in Erzincan-1992, Dinar-1995 and Kocaeli-1999 earthquakes in Turkey utilizing two probability models-Modified Binomial Distribution (MBiD) and Modified Beta Distribution (MBeD). Based on these analyses, it was possible (a) to compare the advantages and limitations of the two probability models with respect to their capabilities in modelling the observed damage distributions; (b) to evaluate the damage assessment for reinforced concrete and masonry buildings in Turkey based on these models; (c) to model the damage distribution of different sub-groups such as buildings with different number of storeys or soil conditions according to the both models. The results indicate that (a) MBeD is more suitable than the MBiD to model the observed damage data for both reinforced concrete and masonry buildings in Turkey; (b) the sub-groups with lower number of stories are located in the lower intensity levels, while the sub-groups with higher number of stories depending on local site condition are concentrated in the higher intensity levels, thus site conditions should also be considered in the assessment of the intensity levels; (c) the detailed local models decrease the uncertainties of loss estimation since the damage distribution of subgroups can be more accurately modelled compared to the general damage distribution models.
Keywords: Earthquake; Damage; Probability matrices; Binomial distribution; Beta distribution; Vulnerability; Geology; Meteorology & Atmospheric Sciences; Water Resources